Managing the suffocation of education sector during the COVID-19 pandemic : a critique of human migration - Modiba, Ngwako Solomon (African Journal of Development Studies (AJDS), 2024)
This paper investigated the coping mechanisms of the higher education sector during the COVID-19 pandemic from the point of view of the restricted human migration. This paper is conceptual and empirical in nature within the qualitative research paradigm. Interviewing technique and narrative enquiry were employed to generate data pertaining to the restricted human mobility during the COVID-19 pandemic. Out of the population of 26 public higher education institutions, in South Africa, only two were conveniently sampled for intensive study on restricted human migration of their employees during the COVID-19 lockdown. This paper is therefore, a case study of two public higher education institutions. Research findings revealed that firstly, organisational efficacy took a nosedive during the COVID-19 pandemic. Secondly, there was a controversy of the mandatory immunisations within the migrants. Thirdly, the application of migration segregation aggravated the state of affairs. Fourthly, the inhibition of the already planned face-toface conference attendance crippled the education sector. Lastly, compromising of quality assessment practices particularly at institutions of higher learning was a disservice and disruptions to the education sector. The study recommended the exemption of the education sector from the suffocation of restrictive health protocols in case of similar COVID-19 pandemics in future.
Journal article published in African Journal of Development Studies (AJDS) Published consistently since 2012 Special Issue, October 2024 pp 147-171
Keywords: Compromise; Conference; Efficacy; Immunisation; Pandemic; Segregation; Immunisation; COVID-19 Pandemic, 2020-2023 -- Influence